2018
DOI: 10.1002/pon.4902
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Malay cultural beliefs on breast cancer screening and genetic testing: A focus group study

Abstract: Objective: Malays comprise an Asian cultural group reported to have low breast cancer screening uptake rates and poor cancer outcomes. Little is known about Malay cultural factors influencing beliefs and practice of cancer screening and genetic testing. Our study aims to explore health beliefs of Malay women around breast cancer screening and genetic testing. Methods:We conducted focus groups among healthy English-speaking Malay women in Singapore, aged 40 to 69 years, using a structured guide developed throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 34 publications
(56 reference statements)
3
48
1
Order By: Relevance
“…Asian women seem to be more conservative as only 53% of respondents in a study did breast self-examinations (Sim et al, 2009;Tan et al, 2005) reported that, between 2000 and 2003, 21.5% of women in Singapore presented with stage III or IV breast cancer which may potentially be due to cultural attitudes toward breast cancer screening tests and modesty, which inhibit Asian women from participating in breast cancer screening (Parsa et al, 2006). Spiritual and religious beliefs were found to act as a barrier to breast cancer screening in Singaporean Malay women (Shaw et al, 2018). As expected, more than half of our female SPs were uncomfortable with breast examination.…”
Section: Resultssupporting
confidence: 65%
“…Asian women seem to be more conservative as only 53% of respondents in a study did breast self-examinations (Sim et al, 2009;Tan et al, 2005) reported that, between 2000 and 2003, 21.5% of women in Singapore presented with stage III or IV breast cancer which may potentially be due to cultural attitudes toward breast cancer screening tests and modesty, which inhibit Asian women from participating in breast cancer screening (Parsa et al, 2006). Spiritual and religious beliefs were found to act as a barrier to breast cancer screening in Singaporean Malay women (Shaw et al, 2018). As expected, more than half of our female SPs were uncomfortable with breast examination.…”
Section: Resultssupporting
confidence: 65%
“…A literature review of CRC screening research revealed two significant issues. First, although many researchers reported that culturespecific health beliefs significantly influenced cancer screening behaviors in diverse racial and ethnic groups (Lee, 2015;Lu et al, 2016;Shaw et al, 2018), only a few studies examined health beliefs about CRC screening behavior as factors that influence CRC screening utilization in Koreans (Bae, Park, & Lim, 2014;. Most CRC screening studies focused on the demographic characteristics and health behavioral factors (e.g.…”
mentioning
confidence: 99%
“…By contrast, the rates of adherence to MAM at one point during the womens' lifetimes varied between 29.9 and 90%, with x=63.5% and M=71%. Regarding adherence to CBE in the last 2 years, the rates ranged from 5.6 to 31.9%, with x=18.7% and M=18.6% (details are available in Table SI) (17)(18)(19)(20)(23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Resultsmentioning
confidence: 99%
“…Factors associated with the participants culture and religion were mentioned in a few articles, most of which had a qualitative design. Shaw et al (29) revealed, through focus groups, that spiritual and religious beliefs (for example, Aurat, fatalism and black magic) play an important role in BC screening among Malay women in Singapore. Furthermore, the confidence in traditional medicine and the distrust in western practices among those women, as well as the role of family and community ties and shared beliefs, were also among the factors mentioned.…”
Section: Resultsmentioning
confidence: 99%